2001
DOI: 10.1099/0022-1317-50-12-1095
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in nasopharyngeal carriage of respiratory pathogens in healthy Italian children attending day-care centres or schools

Abstract: The aim of this study was to investigate seasonal variations in the prevalence of the nasopharyngeal carriage of respiratory pathogens and identify factors affecting colonisation patterns in healthy children. The nasopharyngeal carriage of Streptococcus pneumoniae, Haemophilus in¯uenzae and Moraxella catarrhalis during two seasons (autumn and spring) was evaluated in 1580 healthy children aged 1±7 years by means of a cohort study conducted in day-care centres and schools in eight Italian cities. A questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 14 publications
0
35
1
Order By: Relevance
“…Respiratory pathogens are recovered from the nasopharynx of healthy children throughout the year (33); however, some authors (37,39) have reported seasonal differences in the rates of colonization, with a peak in the winter. In other studies (21,34), the seasonal effect for colonization by S. pneumoniae, H. influenzae, and M. catarrhalis has been shown to be insignificant or absent. In this study, we made a similar observation between two seasons, winter and spring, and only in the cases of H. influenzae in the crèche and M. catarrhalis in the orphanage we did observe an increase in colonization during the spring (the P value for the crèche in the winter versus the crèche in the spring was Ͻ0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory pathogens are recovered from the nasopharynx of healthy children throughout the year (33); however, some authors (37,39) have reported seasonal differences in the rates of colonization, with a peak in the winter. In other studies (21,34), the seasonal effect for colonization by S. pneumoniae, H. influenzae, and M. catarrhalis has been shown to be insignificant or absent. In this study, we made a similar observation between two seasons, winter and spring, and only in the cases of H. influenzae in the crèche and M. catarrhalis in the orphanage we did observe an increase in colonization during the spring (the P value for the crèche in the winter versus the crèche in the spring was Ͻ0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The rates of H. influenzae carriage in Europe and North America range from 11.7% to 95.0% among children attending DCCs, living in orphanages, or attending schools in various situations (3,5,8,17,18,27,28,31,32,36). Such a wide dispersion may be explained by the fact that the carriage rate is dependent on multiple factors, such as age, season, the size of the facility, antibiotic treatment, morbidity from acute URIs, the sampling technique, and the type of infant feeding (9).…”
Section: Discussionmentioning
confidence: 99%
“…The day-care-center (DCC) attendance of children has been reported to be one of the risk factors for URIs, including acute otitis media (1,4,39), and for the nasopharyngeal carriage of bacteria such as H. influenzae and Streptococcus pneumoniae (7,27,32). However, the molecular epidemiology of H. influenzae in the nasopharynx in connection with DCC attendance is not fully understood (5,8,17,27,29,31,32,36,40,42). The aim of this study was to investigate antibiotic resistance-related genetic characteristics and the turnover of nasopharyngeal H. influenzae carriage in children attending DCCs.…”
mentioning
confidence: 99%
“…nose and throat). The result can be various respiratory infections, as well as invasive diseases (Marchisio et al, 2001;Jacobs et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the human URT, bacterial colonization is a dynamic process in which bacteria are acquired, eliminated and reacquired many times during a human life and can be influenced by various factors such as host age, immune status, exposure to antibiotics, smoking and overcrowded living conditions (Marchisio et al, 2001;García-Rodríguez & Fresnadillo Martínez, 2002;Chen et al, 2007;Mukundan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%